The Stage of Contamination: Performing Environmental Racism through Water in Erika Dickerson-Despenza’s cullud wattah - Holešová, Andrea (American & British Studies Annual, 2025)
The paper examines Erika Dickerson-Despenza’s award-winning play cullud wattah (2021) as a powerful dramatization of environmental injustice centering on the Flint Water Crisis as both a historical event and a symbol of systemic racism in the United States. Through the lens of environmental justice scholarship and the concept of “slow violence,” this analysis explores how race, class, and gender intersect to shape unequal access to clean water. The play foregrounds the lived experiences of a working-class African American family grappling with the physical, psychological, and spiritual consequences of toxic water contamination. The Cooper women represent generational responses to oppression, ranging from resignation and complicity to spiritual resilience and political activism. The staging transforms contaminated water into a powerful symbol of both trauma and resistance, while the absence of theatrical closure emphasizes the unresolved nature of the crisis. Integrating legal, political, and cultural critiques, cullud wattah emerges as a compelling call to action advocating for truth-telling, reparations, and structural change.